Biopsy-Induced Duodenal Hematoma Is Not an Infrequent Complication Favored by Bone Marrow Transplantation. Issue 6 (December 2016) - Sierra, Anaïs; Ecochard-Dugelay, Emmanuelle; Bellaïche, Marc; Tilea, Bogdana; Cavé, Hélène; Viala, Jérôme
ABSTRACT: Objectives: Intraduodenal hematoma (IDH) is an uncommon complication of endoscopic duodenal biopsy that can cause severe obstruction of the digestive, biliary, or pancreatic tracts. We aimed to analyze the risk factors and outcomes of biopsy-induced IDH in our series. Methods: Between 2010 and 2014, a retrospective chart review was conducted for all children younger than 18 years of age treated for IDH. We collected their data in our tertiary pediatric center and compared them to those of controls matched for age, sex, and pathology. Results: Among 2705 upper nontherapeutic endoscopies and 1163 duodenal biopsies, 7 IDH occurred in 6 children suspected of developing graft-versus-host disease (GVHD) after bone marrow transplantation (BMT) and in 1 patient with Noonan syndrome. The IDH prevalence was significantly higher after BMT compared to children who did not undergo grafting (7% vs 0.1%; P  = 7.9 × 10 −7 ; odds ratio = 82). After a median delay of 48 hours, patients developed intestinal obstruction with abdominal pain and vomiting. The diagnosis was confirmed by using ultrasonography or computed tomography scans. Acute pancreatitis was determined in 3 out of 7 patients. Conservative treatment allowed complete resolution in all patients. Conclusions: IDH is not an infrequent complication of endoscopic duodenal biopsy, especially in patients who undergo BMT. Endoscopists should be especially careful during the duodenal biopsy procedure in these patients. With no early perforation due to post-biopsy IDH reported, the prognosis is good and conservative management generally leads to resolution of the symptoms in 2 to 3 weeks. Abstract : Supplemental Digital Content is available in the text